Status Compared to Standards for Early Postemergence Efficacy in Corn - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2025)
The addition of Status herbicide to Halex GT generally increased the control of kochia, Palmer amaranth, and johnsongrass compared to Halex GT alone. The tank mixture of Status plus Zidua SC with or without Callisto was as effective as Resicore, Halex GT plus Status, Acuron GT plus Status, and Callisto plus Sequence and Status on kochia and Palmer amaranth. Diflexx Duo plus atrazine controlled kochia and Palmer amaranth similarly to the Status tank mixtures, but was less effective on johnsongrass. Grain yields increased 9- to 14-fold with all herbicide-treated corn relative to the untreated controls.
Keywords: Tank mixtures; residual control